Efisiensi Pengeluaran Pemerintah Sektor Kesehatan di Kabupaten/Kota Provinsi Banten - Siti Fatimah Humairah; Fitri Amalia; Aisyah Mutiara Putri (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2026)
The efficiency of government expenditure in the health sector is an important factor in supporting the achievement of health development, particularly in improving Life Expectancy (LE). Banten Province has experienced a continuous increase in health budget allocations over time; however, its life expectancy remains relatively low compared to other provinces on Java Island. This study aims to analyze the efficiency of government health sector expenditure across regencies and cities in Banten Province during the period 2019–2023. The analytical method employed is Data Envelopment Analysis (DEA) using an output-oriented Variable Returns to Scale (VRS) approach. The input variables include the Health Operational Assistance (BOK) budget, the percentage of BPJS Contribution Assistance Recipients (PBI), and the number of community health centers (Puskesmas), while Life Expectancy is used as the output variable. The results indicate that only South Tangerang City consistently achieved optimal efficiency throughout the study period, whereas the other seven regencies and cities failed to reach full efficiency. These findings suggest that the increase in health budget allocations has not been fully accompanied by effective resource management. Therefore, strengthening planning, supervision, and the equitable distribution of health services is necessary to improve expenditure efficiency and regional health development outcomes.